EFEKTIVITAS EDUKASI MELALUI APLIKASI MPASI TERHADAP PENGETAHUAN IBU - Rezah Andriani; Ingge Anggi Anggarini; Frenalia Valeri Valencia (Jurnal Delima Harapan, 2022)
Abstract Lack of awareness and knowledge of mothers about good nutrition given to children plays an important role in maintaining the quality of the food provided. For this reason, it is necessary to make an educational application about MPASI that helps mothers in accessing information about how to present MPASI properly and correctly. The purpose of this study was to determine the effectiveness of education through the MP-ASI application on maternal knowledge at PMB Herasdiana and PMB Zuniawati Palembang in 2021. This study used a quantitative approach, the method used in this study was a quasi-experimental type of pre-post test control group design. The results of the study, the use of education through the MPASI application was 1.5 times more effective than education through leaflets in increasing Mother's Knowledge about MPASI with a score of 5. The use of education through the MPASI application was 6.5 times more effective than education through leaflets in increasing Mother's Knowledge about how to give MPASI with a score of 5.5.